OPTIMIZING THE DESIGN OF COMPLETE DENTURES FOR PROSTHETIC STOMATITIS PREVENTION - A.A. Zverkhanovskyi; A.V. Yarova; P.V. Maksimenko (Український стоматологічний альманах)
The aim of the paper is to evaluate the impact of the developed design with the use of amaranth oil of the mucous membrane of oral cavity and hard tissues of the alveolar bone.